EFFECT OF SUGAR SUBSTITUES ON WHEAT DOUGH RHEOLOGY - ELENA-MADALINA STEFAN; GHEORGHE VOICU; GABRIEL-ALEXANDRU CONSTANTIN; GABRIELA-MARIANA MUNTEANU; GEORGE IPATE (Scientific Study & Research: Chemistry & Chemical Engineering, Biotechnology, Food Industry)
High intake of added sugars has many negative effects on human health. This is the reason why in recent years the replacement of sugar (sucrose) in food and drinks by natural and artificial sweeteners (low-calorie) has increased significantly. The sugar plays an essential role in technology of bakery and pastry products. The purpose of this article is to evaluate the effect of sugar substitutes on rheological properties of wheat dough. Erythritol and stevia (nutritious sweetener) have been used as sugar substitutes. The sugar and sweeteners were added in white wheat flour at levels of 0-5% (the rheological properties of 100 % white wheat flour was determinate for comparison). Effects were seen on the dough rheology, which were evaluated by farinographic characteristics with Brabender Farinograph-E with electronic measuring system, according to AACC No. 54-21, ICC No. 155/1. Water absorption decreased with the increase of both sweeteners ratio because the protein and complex carbohydrates contents are reduced. The dough development time varied non-significantly with addition of sweeteners (from 1.7 to 2.2% for both sweeteners, stevia and erythritol). The dough stability time increased significantly from 1.7 to 2.6 min in both cases of sweeteners adding. The degree of softening values decreased with the supplementation of both with stevia and with erythritol. The Farinograph Quality Number values increased more with stevia supplementation, from 25 to 78, and up to 43 for erytrithol added. The obtained results are important for the specialists of the bakery technological process.